PELAKSANAAN SALAT SANTRI PUTRI PERSPEKTIF KITAB SAFĪNATUN NAJĀH DI PONDOK PESANTREN TANBIHUL GHOFILIN BAWANG BANJARNEGARA - Rofi’ah, Laelatul; Sunarko, Asep; sofwan, Muhtar (STAI Denpasar Bali, 2023)
This study aims to describe the implementation of female students' prayers from the perspective of the Book of Safīnatun Najāh held at the Tanbihul Ghofilin Islamic Boarding School. The focus of this thesis is (1) knowing the implementation of Santri Putri Prayers from the perspective of the Book of Safīnatun Najāh at the Tanbihul Ghofilin Islamic Boarding School; (2) knowing the efforts of the Tanbihul Ghofilin Islamic Boarding School in improving the implementation of Santri Putri Prayers; and (3) knowing things that support and hinder the implementation of Santri Putri Prayers according to the Book of Safīnatun Najāh at the Tanbihul Ghofilin Islamic Boarding School. The research objects were: (1) a board of trustees for the Safīnatun Najāh Book program; (2) teachers or ustadzah for the Safīnatun Najāh Book program; (3) a board of trustees of the Tanbihul Ghofilin Islamic Boarding School for the Safīnatun Najāh Book program; and (4) Santri Pondok Pesantren Tanbihul Ghofilin Book of the Safīnatun Najāh program. The approach used is descriptive-qualitative. The techniques used to collect data in this research are observation, interviews, and documentary studies. The discussion shows that the Tanbihul Ghofilin Islamic Boarding School teaches prayers with the Book of Safīnatun Najāh through guidance, simulation, practice, and applying habituation. The supporting factors are cooperation between the Head of Madrasah Diniyah and Ustadzah, the support of female students' parents, and the facilities available. While the inhibiting factors are worldliness and limited infrastructure, there are still deficiencies in the implementation of prayers from the perspective of the Book of Safīnatun Najāh